About the influence of neglecting locking effects on the failure behavior at the interface. Issue 1 (25th January 2021) - Bayat, Hamid Reza; Rezaei, Shahed; Rajaei Harandi, Ali; Brepols, Tim; Reese, Stefanie
Abstract: In the present work, a novel cohesive discontinuous Galerkin (CDG) method is proposed to model interfacial failure of brittle materials. Before the failure, an incomplete interior penalty Galerkin (IIPG) variant of discontinuous Galerkin (DG) family is applied for the linear elasticity. Once the failure criterion is met, an extrinsic cohesive zone (CZ) model captures the failure behavior of the interface. Through application of the DG method in combination with reduced integration on the boundary terms, the locking problem of the bulk elements is solved as well as a realistic propagation of the crack is obtained. In addition, due to the presence of the DG elements prior to failure, remeshing of the interface during crack propagation is not required for the proposed extrinsic CZ model. Delamination of a composite structure is simulated in a numerical example. Furthermore, the performance of the CDG element formulation in comparison to a conventional intrinsic CZ element is discussed and conclusions are drawn.